2021
DOI: 10.3390/ijerph19010195
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping Strategies of Nurses Working with Patients Infected with and Not Infected with SARS-CoV-2 Virus

Abstract: Introduction: Working during the COVID-19 pandemic is a particular challenge for nurses because, while performing their daily routines, they are exposed to physical and social consequences of the SARS-CoV-2 virus, which is accompanied by intensified stress. The aim of this study was to assess the intensity of stress and coping strategies applied by nurses working with both infected and non-infected patients with SARS-CoV-2 virus during the COVID-19 pandemic. Materials and Methods: The study was conducted betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Yet these results are inconsistent with Puto et al (2022) who showed no significant correlations between the intensity of perceived stress and nurses' age, both in the case of nurses working with SARS-CoV-2-infected patients and those working with non-infected ones.…”
Section: Discussioncontrasting
confidence: 82%
“…Yet these results are inconsistent with Puto et al (2022) who showed no significant correlations between the intensity of perceived stress and nurses' age, both in the case of nurses working with SARS-CoV-2-infected patients and those working with non-infected ones.…”
Section: Discussioncontrasting
confidence: 82%
“…We conducted our study to assess the perceived stress in two groups of students of one medical faculty but at different stages of life, taking into account that the first group was just starting their education and the second group was almost at its end. This factor could probably be one of the determinants of the differences in perceived stress, which was more intense among students in the first year of studies (22.22 ± 5.71 points) and was comparable to the level reported in the group of nurses working with patients infected with SARS-CoV-2 (22.22 ± 5.94 points) [ 30 ]. Stress was more intense among students in the first year of studies.…”
Section: Discussionmentioning
confidence: 75%
“…Another Polish study by Puto et al [ 30 ] involved 151 nurses working with patients infected with SARS-CoV-2 and patients who were not infected during the COVID-19 pandemic. Nurses working with patients who had SARS-CoV-2 experienced more stress than those working with uninfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses working with patients who had SARS-CoV-2 coped with stress using strategies focused on the problem (active coping, seeking instrumental support) and on emotions (seeking encouragement, understanding and support from other people). On the other hand, nurses working with uninfected patients most often chose strategies focused solely on the problem (active coping and planning) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%